2015
DOI: 10.1021/acs.jpcc.5b04532
|View full text |Cite
|
Sign up to set email alerts
|

Photomagnetic Carbon Nanotubes at Ambient Conditions

Abstract: KEYWORDSbis(2,2-bipyridine)-5-amino-1,10-phenanthroline ruthenium(II), carbon nanotube, diazotization, photoinduced charge transfer, photomagnetism ABSTRACT Bis(2,2-bipyridine)-5-amino-1,10-phenanthroline ruthenium(II) (Ru(bpy) 2 (phen-NH 2 ) 2+ ), an MLCT complex, has a long-lived triplet state in water (λ ex :473 nm; λ em : 620 nm; τ = 615 ns; Φ = 1 relative to that of Ru(bpy) 3 2+ ) and a structure analogous to Ru(bpy) 3 2+ . When Ru(bpy) 2 (phen-NH 2 ) 2+ was subjected to diazotization in the presence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…We consider this an indication that the ruthenium compound is mainly adsorbed on the preadsorbed APBA instead of the host, which supports the mechanism proposed in Scheme 1. The Ru|APBA|CNT tube exhibits photomagnetism towards external magnets at room temperature as floating on water, similar to the tubes modified with Ru(bpy) 2 (phen-NH 2 ) 2+ [5]. The average mobility measured for the photo-illuminated Ru|APBA|CNTs ( ex : 473 nm; 27 mW) on water was 0.3 mm/min (65 Gauss).…”
Section: åmentioning
confidence: 74%
See 2 more Smart Citations
“…We consider this an indication that the ruthenium compound is mainly adsorbed on the preadsorbed APBA instead of the host, which supports the mechanism proposed in Scheme 1. The Ru|APBA|CNT tube exhibits photomagnetism towards external magnets at room temperature as floating on water, similar to the tubes modified with Ru(bpy) 2 (phen-NH 2 ) 2+ [5]. The average mobility measured for the photo-illuminated Ru|APBA|CNTs ( ex : 473 nm; 27 mW) on water was 0.3 mm/min (65 Gauss).…”
Section: åmentioning
confidence: 74%
“…The bare CNTs remained unmoved under similar conditions. The CNT tubes shown in Figure 6 were also investigated for their magnetic properties by the magnetic-mode AFM (MFM) [5,22]. As shown in Figure 8, the oscillation of the MFM tip changes negligibly (curves (A) and (B)) as the tip is set 4 nm atop APBA|CNT at spots (A) and (B), regardless of lights ( : 473 nm, 26 mW) on (L) and off (D).…”
Section: åmentioning
confidence: 99%
See 1 more Smart Citation
“…Veracity explains about value and quality of data that is stored. North American Disease Spread Model it was developed with broad international carries to help policy evolution and disease incursions [4] .…”
Section: Big Datamentioning
confidence: 99%
“…Mohebkhah and Farahani showed that by considering the effects of SSI in direct displacement‐based design of steel eccentrically braced frames, the base shear decreases, which may result in an economical design of such frames. Some research was carried out about the SSI effect on the vibration control effectiveness of an irregular building subjected to earthquake excitations . In such model, there is a large torsion around z direction, simultaneously with the lateral displacement in both x and y directions.…”
Section: Introductionmentioning
confidence: 99%